University students´ emotions in forced remote education - Elisondo, Romina Cecilia (2023)
In 2020, due to the COVID-19 pandemic, universities had to suddenly and forcefully implement remote education. The study had three objectives: to explore and compare university students´ emotions; to analyze the associations between emotions and socioeducational factors; and to understand, from the student's perspective, emotions and experiences lived during remote education. The study was exploratory and comparative. The analyses were quantitative and qualitative. Five hundred and eighty students from the University of Extremadura (Spain) and the University of Río Cuarto (Argentina) participated. Data collection was carried out between May and September 2020. Two data collection instruments were used: self-administered online questionnaire and focus groups. The results indicated concern about connectivity and lack of technological resources. The predominance of negative emotions and communication difficulties was observed in both quantitative and qualitative data. However, we also found flexible and adaptive practices that had allowed students to cope with communication difficulties, and unfavorable emotional states.